Experimental study on thermal runaway and its propagation of large format prismatic lithium-ion batteries. (25th November 2022) - Wang, Boxuan; Zhou, Zhizuan; Li, Lun; Peng, Yang; Cao, Junda; Yang, Lizhong; Cao, Bei
Abstract: Lithium-ion batteries (LIBs) are one of the most promising technologies in electric vehicles and electric energy storage systems. However, safety accidents related to TR (thermal runaway) often occur. At present, large-format prismatic batteries have been put into use as part of the energy storage system. In practice, batteries often appear in the form of modules, which also increases the risk of TR control. The phenomenon of TR propagation of prismatic lithium-ion battery in modules is rarely studied. In this study, the TR behaviors of the single battery and module were investigated through overheating experiments. The results showed that the highest spontaneous-heating power of batteries with 0 %, 50 % and 100 % SOC (State of charge) are 67 W, 1336 W and 2308 W, respectively. Experiments also performed TR propagation experiments between monolayer and bilayer cell modules, which showed that TR is transmitted in the monolayer module, but not in different layer modules. In addition, compared with the single battery, the TR of the battery module in the propagation process is more intense, and the TR is most likely to fail in the propagation process of the second and the third battery. To gain a comprehensive understanding of the TR propagation of the prismatic LIB modules, a method to determine whether the TR will spread is achieved based on the spontaneous thermal power. This study further reveals the propagation behavior of heat abuse of prismatic lithium batteries, and its results provide guidance for the safety design and thermal hazard prevention of battery storage systems. Highlights: A model based on heat production is proposed to judge whether the battery will have thermal runaway. The maximum spontaneous heat value of the battery under different SOC is revealed. The TR propagation in high-capacity prismatic lithium-ion battery modules is revealed. The difficulty of TR propagation between cells in the module has been compared. The deficiency of the previous research on thermal runaway of high-capacity prismatic battery is supplemented.